Unveiling the Impact of Different Nitrogen Fertilizer Levels on Rice’s Eating Quality through Metabolite Evaluation - Nianbing Zhou; Yanhong Zhang; Tong Sun; Jinyan Zhu; Jinlong Hu; Qiangqiang Xiong (Agronomy, 2023)
We investigated the variations in metabolites associated with the quality of rice consumption when exposed to varying nitrogen fertilizer levels, as well as the regulatory role of pivotal metabolites within metabolic pathways. This research employed Hongyang 5 as the subject of experimentation, examining the metabolites of Hongyang 5 at three different nitrogen levels using non-targeted metabonomic analysis. The findings indicated that the overall assessment of the eating quality/palatability (CEQ) and amylose contents (AC) of Low nitrogen (D1: 180 kg·ha−1) was notably greater than that of Medium nitrogen (D2: 270 kg·ha−1) and High nitrogen (D3: 315 kg·ha−1). Conversely, the amylopectin (APC), total starch (SC), and protein contents (AP) of D1 were remarkably lower than those observed in D2 and D3. The starch debranching enzyme (DBE) and granule-bound starch synthetase (GBSS) of D1 were remarkably higher than those of D2 and D3. The soluble starch synthase (SSS) of D1 was the lowest. The ADP-glucose pyro-phosphorylase (AGP) and starch branching enzyme (SBE) of D3 were remarkably higher than that of D1 and D2. We identified 76 differential metabolites (DMs) between D1 and D2 (20 up-regulated and 56 down-regulated). A total of 88 DMs were identified between D3 and D1 (42 up-regulated and 46 down-regulated). A total of 57 DMs were identified between D3 and D2. Most of the DMs related to rice-eating quality were involved in the lipid metabolic pathway and amino acid metabolic pathway. The essential metabolites within the metabolic pathway are classified as lipid metabolites and are (13(S)-hydroperoxylinolenic acid, PGB2, 3-phosphocholine, 7-epijasmonic acid, 20-carboxyleukotriene B4 and 11-dehydro-thromboxane B2), amino acid metabolites (4-guanidinobutanoic acid, (3R, 5S)-1-pyrroline-3-hydroxy-5-carboxylic acid, citric acid, (S)-2-Acetolactate, L-glutamine, L-2, 4-aminobutyric acid and putrescine). These key metabolites may be affected by nitrogen fertilizer conditions and play critical regulatory roles in the metabolic pathway, resulting in differences in rice eating quality.